2021
DOI: 10.1186/s13148-021-01164-9
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal risk factors and neonatal DNA methylation in very preterm infants

Abstract: Background Prenatal risk factors are related to poor health and developmental outcomes for infants, potentially via epigenetic mechanisms. We tested associations between person-centered prenatal risk profiles, cumulative prenatal risk models, and epigenome-wide DNA methylation (DNAm) in very preterm neonates. Methods We studied 542 infants from a multi-center study of infants born < 30 weeks postmenstrual age. We assessed 24 prenatal risk factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…Moreover, as we observed heightened epigenetic age in wild compared to lab mice even during the first ∼2 weeks of life, we suggest that peri- and early postnatal effects on offspring DNA methylation may vary between laboratory and wild mice and contribute to their different epigenetic age profiles. Various human, mouse, and other animal studies have demonstrated the association between prenatal maternal experience (such as food shortage, diet, infection, substance exposure, and stress) and offspring DNA methylation patterns, with differences from the prenatal (foetal) phase still detectable in later life (Tobi et al, 2009; Heijmans et al, 2008; Lan et al, 2013; Richetto et al, 2017; Camerota et al, 2021; Joubert et al, 2016; Kertes et al, 2016; Vangeel et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as we observed heightened epigenetic age in wild compared to lab mice even during the first ∼2 weeks of life, we suggest that peri- and early postnatal effects on offspring DNA methylation may vary between laboratory and wild mice and contribute to their different epigenetic age profiles. Various human, mouse, and other animal studies have demonstrated the association between prenatal maternal experience (such as food shortage, diet, infection, substance exposure, and stress) and offspring DNA methylation patterns, with differences from the prenatal (foetal) phase still detectable in later life (Tobi et al, 2009; Heijmans et al, 2008; Lan et al, 2013; Richetto et al, 2017; Camerota et al, 2021; Joubert et al, 2016; Kertes et al, 2016; Vangeel et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Preterm birth has been shown to leave an epigenetic signature that persists into adolescence and adulthood (Cruickshank et al, 2013; Tan et al, 2018). Prenatal risk, measured cumulatively and as distinct phenotypes, has been shown to predict DNA methylation at birth at multiple specific CpG sites across the epigenome in children born < 30 weeks (Camerota et al, 2021). In this study, prenatal risk was primarily associated with lower DNA methylation, and many of the identified CpGs were located in genes previously shown to be associated with physical and mental health outcomes as well as neurodevelopmental markers (Camerota et al, 2021).…”
Section: Prenatal Risk In Children Born Very Pretermmentioning
confidence: 99%
“…Prenatal risk, measured cumulatively and as distinct phenotypes, has been shown to predict DNA methylation at birth at multiple specific CpG sites across the epigenome in children born < 30 weeks (Camerota et al, 2021). In this study, prenatal risk was primarily associated with lower DNA methylation, and many of the identified CpGs were located in genes previously shown to be associated with physical and mental health outcomes as well as neurodevelopmental markers (Camerota et al, 2021). Further candidate gene and epigenome-wide findings in preterm children show associations between DNA methylation and bacterial sepsis (Tendl et al, 2013), pain-related stress (Chau et al, 2014; Provenzi et al, 2015), medical morbidities (Everson et al, 2020), and neonatal neurobehavior (Everson et al, 2019; Lester et al, 2015).…”
Section: Prenatal Risk In Children Born Very Pretermmentioning
confidence: 99%
“…23,240 Most work has been done in diseases of adulthood, but these data could provide useful insights into the susceptibility and pathogenesis of many neonatal conditions. [241][242][243]…”
Section: Role Of Iim Macrophage In Diseases In Adult Patients/animal ...mentioning
confidence: 99%